(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to investigate data security in cloud computing, analyzing the security threats facing data stored and processed in cloud environments, and reviewing preventive solutions and techniques to ensure its protection. The research problem focuses on the diversity of threats and their impact on data confidentiality, integrity, and availability, including unauthorized access, data leakage, malicious attacks, API exploitation, and data loss. The study reviews previous research, classifies threats according to the CIA model (Confidentiality, Integrity, Availability), and presents a comprehensive table illustrating the threats, practical examples, and their relation to prior studies. It also explores technical and administrative solutions, such as encryption, access control, multi-factor authentication, regular backups, continuous monitoring, and modern security models like Zero Trust. The findings indicate that securing cloud data requires a combination of technical measures, security policies, and user awareness training. Moreover, applying best practices significantly reduces incidents of data breaches and enhances the trust of organizations and users in cloud services. Based on these results, the study recommends implementing integrated preventive measures, strengthening national security policies, and raising user awareness to ensure effective cloud data protection.